The Relationship between Safety Management Systems, Safety Performance and Customer Satisfaction in the Australian Construction Industry: A Quantitative Research Proposal - Eldejany, Raed (Journal of Research in Marketing (ISSN: 2292-9355), 2019)
Although the number of work health and safety (WHS) research in construction has increased over the past 15 years, there is still limited research in the area of safety management system (SMS) and its impact on organizational outcomes such as customer satisfaction. The main objective of this research proposal is to provide the foundation for a potential future study that explores the relationship between safety management system, safety performance and customer satisfaction from the prospective of 383 site supervisors in Australian construction business using a multiple regression quantitative approach. A positive relationship between SMS, safety performance and customer satisfaction will support the business case for developing and implementing SMS in construction business and motivate management to invest in WHS.